An experimental investigation on the ultimate strength of braced reinforced concrete infilled frames - Dubey, Shailendra Kumar; Kute, Sunil (Journal of Structural Engineering, 2024)
Infilled walls are normally considered as non-structural elements. However these walls are effective in carrying lateral loads. The main aim of the present experimental study is to observe the failure crack pattern and also to find the contribution of Braced Reinforced Concrete (BRC) infilled frames in resisting deflection and lateral loads. This study consists of testing ten models of single bay, single storey reinforced concrete infilled steel frames with corner, full top corner and diagonal steel bracings. The behaviour of such frames subjected to lateral loads alone has been considered and constructive conclusions are drawn. The BRC infilled frames have significant less deflection in comparison to reinforced concrete infilled frames for similar load. Based on experimental observations, a mathematical model has been proposed to calculate theoretical ultimate load for BRC infilled frames.